2018
DOI: 10.1007/s00192-018-3652-0
|View full text |Cite
|
Sign up to set email alerts
|

Survey of pelvic reconstructive surgeons on performance of opportunistic salpingectomy at the time of pelvic organ prolapse repair

Abstract: OS at the time prolapse repair is performed more frequently with concomitant hysterectomy compared with OS at the time of post-hysterectomy prolapse repair and is similar to rates of OS performed at the time of hysterectomy for non-prolapse indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Garcia et al demonstrated that in 16.5 % of cases, salpingectomy is performed with vaginal hysterectomy, while in 55.8 % of cases, salpingectomy is performed with hyster¬ectomy via other routes. [15] According to studies that have examined the surgeons' tendency about salpingectomy during vaginal hysterectomy, the majority of physicians not perform salpingectomies due to the affair of increase in complications, increased operating room time and increased estimated blood loss with the addition of salpingectomy [15,16]. But in our study, there was no difference in operating time, median estimated blood loss, intraoperative complication and postoperative complication by the performance of salpingectomy (P>0.05).…”
Section: Discussionmentioning
confidence: 51%
“…Garcia et al demonstrated that in 16.5 % of cases, salpingectomy is performed with vaginal hysterectomy, while in 55.8 % of cases, salpingectomy is performed with hyster¬ectomy via other routes. [15] According to studies that have examined the surgeons' tendency about salpingectomy during vaginal hysterectomy, the majority of physicians not perform salpingectomies due to the affair of increase in complications, increased operating room time and increased estimated blood loss with the addition of salpingectomy [15,16]. But in our study, there was no difference in operating time, median estimated blood loss, intraoperative complication and postoperative complication by the performance of salpingectomy (P>0.05).…”
Section: Discussionmentioning
confidence: 51%